2020
DOI: 10.3390/ijerph17114144
|View full text |Cite
|
Sign up to set email alerts
|

Exercising in Times of Lockdown: An Analysis of the Impact of COVID-19 on Levels and Patterns of Exercise among Adults in Belgium

Abstract: Countries all over the world implemented lockdowns to counteract COVID-19. These lockdowns heavily limited people’s exercise possibilities. At the same time, experts advocated to remain physically active to prevent future health problems. Based on an online survey, this study examines adults’ exercise levels and patterns during the COVID-19 lockdown in Belgium. Ordinal logistic regression analyses of 13,515 valid and population-weighted responses indicate a general increase in exercise frequencies, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
402
11
31

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(489 citation statements)
references
References 22 publications
45
402
11
31
Order By: Relevance
“…Here, we observed that responders reported a decrease in their weekly overall, moderate and intense PAs ( Figure 1 B); which was also independently correlated with a deterioration in their well-being ( Table 1 ). These results are consistent with two recent studies about COVID-19 lockdown in Portugal [ 20 ] and Belgium [ 21 ], in which both reported a decrease in energy expenditure during COVID-19 lockdown. We can therefore think that the lack of PA is a determining factor in the well-being under lockdown.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we observed that responders reported a decrease in their weekly overall, moderate and intense PAs ( Figure 1 B); which was also independently correlated with a deterioration in their well-being ( Table 1 ). These results are consistent with two recent studies about COVID-19 lockdown in Portugal [ 20 ] and Belgium [ 21 ], in which both reported a decrease in energy expenditure during COVID-19 lockdown. We can therefore think that the lack of PA is a determining factor in the well-being under lockdown.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with our previous investigation, which showed that during home-confinement 48.6% of the participants from the same student population decreased their PA levels, and with other research performed with college students and adults from the United States of America and France, respectively [ 16 , 26 , 27 ]. Indeed, another study carried out in Belgium by Constandt et al reported a general increase of exercise, even with a concomitant increase of sedentary behaviors, in the Belgian adult population during the CoViD-19 lockdown [ 28 ]. These contrasting results were due to the fact that people who were previously under-active reported exercising more during the lockdown; while, among individuals who were already highly active before the pandemic, those above 55 years old, those with low education, those who used to exercise with friends or in a sport club, and those who were not using online tools to exercise, reported exercising less during home-confinement.…”
Section: Discussionmentioning
confidence: 99%
“…We posit that this is probably a consequence of the greater amount of free time available due to the increased rate of unemployment (22.7%; (95%CI 20.8–24.6)) during lockdown, or perhaps due to the natural body’s need for physical activity against inactivity, for volitional reaction against a sedentary style of life, or for health reasons [ 26 ]. Similarly, in two relevant studies in people aged 55+ (years, previously low activity) and body weight lifters, there was a slight increase in PA during lockdown, but it was not clear whether this increment resulted from leisure, sports, or other PA [ 30 , 31 ]. However, in our study, the augmented EE during leisure time activities did not compensate for the overall decremented EE during daily occupational, transportation, or sporting activities due to quarantine.…”
Section: Discussionmentioning
confidence: 99%